Outer Membrane Proteins as Vaccine Targets Against Lawsonia intracellularis in Piglets - Kara L. Aves; Ana H. Fresno; Sajid Nisar; Mauro M. Saraiva; Nicole B. Goecke; Adam F. Sander; Morten A. Nielsen; John E. Olsen; Priscila R. Guerra (Vaccines)
Background: Lawsonia intracellularis (LI) is the agent of proliferative enteropathy in swine, a common disease that affects pigs for up to eight weeks after weaning. Aim: To evaluate the effectiveness of two novel subunit vaccines targeting outer membrane proteins on LI. Methods: The two vaccines included OMP2c.cVLP, where the OMP2c antigen was anchored on the surface of capsid virus-like particles (cVLP); and MBP.INVASc, where antigens were anchored to an MBP fusion protein. Groups of six mice, as proof of concept, and six piglets were immunized with either OMP2c.cVLP, MBP.INVASc., or PBS as a control using a prime-boost regime. Results: Both OMP2c.cVLP and MBP.INVASc subunit vaccines induced strong antigen-specific serum IgG and IgA responses. There were no significant differences in weight gain among the groups. Mild-to-moderate clinical signs of LI infection were observed, but vaccinated groups showed lower inflammatory scores and fewer animals tested positive for bacteria by immunohistochemistry. Although neither vaccine completely prevented clinical signs of LI infection, both effectively reduced inflammation and lowered the pathogen load, thereby mitigating the severity of the disease, particularly the MBP.INVASc vaccine. Conclusions: These findings suggest that both vaccines have the potential for further development and optimization to enhance their protective efficacy against LI infections.